An Assessment of Nigeria Security Sector Reform, 1999-2010 - Mohammed, Abubakar Ahmad (International Studies Journal)
This research work is necessitated by the poor perception and understanding of the security sector in Nigeria. Prolonged military rule in Nigeria undermined professionalism of the security forces.   This is as a result of lack of effective civilian oversight or relations.  This research paper set out with four objectives:   First to examine the place of security sector reform in Nigeria, and second to examine the programmes and policies on security sector reform in Nigeria.  Thirdly, to determine the challenges facing security sector reform in Nigeria.  Finally, to propose necessary strategies for successful security sector reform in Nigeria. The research work was mainly descriptive in nature and the study relied mainly on primary and secondary sources. The major findings were that the programme Military Professionals Resources Incorporated was the major security sector reform programme which embarked upon by President O. Obasanjo administration and that security sector is those organisations, which have authority to use or order the use of force or the threat of force, to protect the state and its citizens, as well as those civil structures that are responsible for their management and oversight. The research findings were that security sector reform reflects those policies, legislations and actions taken by governments to ensure that the security sector provides safety for the citizens efficiently and effectively without inhibitions.  However, the outcome of this research should be useful to the security agencies as well as policy makers in Nigeria.